Analysis Of Slope Stability Based On The Effect Of Rainfall On The Lombok International Airport (Bil) - Mandalika Road Sta 10+375 To Sta 10+550 - Sudiadnya, Made; Khoiri, Mohamad; Warnana, Dwa Desa; Zulfikar, Herlambang (Journal of Infrastructure & Facility Asset Management, 2025)
BIL - Mandalika Bypass Road connects Lombok International Airport (BIL) to Mandalika Special Economic Zone (KEK). This road has a length of 17.3 KM and was completed in 2021. The construction of this section can cut the travel time from 45 minutes to 15 minutes from BIL to the Mandalika area. In early February 2023 when it was raining season, the BIL - Mandalika Bypass Road surface at sta 10+375 s/d 10+550 experienced cracks, and temporary maintenance had been carried out to keep road remain functional. At the end of May 2023, the cracks became worse and there was a decrease of road surface up to 1.2 to 1.8 meters. Based on the soil test report in the field when the landslide occurred, it shows that the groundwater level is 7.5 meters from the road surface. Laboratory test results show that the subgrade is more dominant sandy silt, besides that the 2024 planning report does not include rain parameters on design of slope stability. The purpose of this study is to determine the effect of rain and groundwater level on landslides and subsidence of the BIL - Mandalika STA 10+375 - 10+550 road in 2023. The simulation results of SEEP/W and SLOPE/W showed that the landslide or subsidence was caused by rain, where the slope safety factor before the landslide was 1.197 and decreased to 0.982 after rainfall happen from Januari 2023 to February 2023.